Physical Activity in Older Cancer Survivors: What Role Do Multimorbidity and Perceived Disability Play? - Bluethmann, Shirley M; Foo, Wayne; Winkels, Renate M; Mama, Scherezade K; Schmitz, Kathryn H (Journal of aging and physical activity, 2020)
(a) To describe the relationship of multimorbidity and physical activity (PA) in cancer survivors and (b) to explore perceived disability and PA in middle-aged and older survivors. The authors analyzed the data from cancer survivors (N = 566), identified using the Pennsylvania Cancer Registry, who responded to a Behavioral Risk Factor Surveillance System-derived questionnaire. They created age groups (e.g., 45-54 years, 55-64 years, 65-74 years, and 75 years and older) and calculated a composite score of eight common comorbidities (e.g., chronic obstructive pulmonary disease, heart disease) to assess multimorbidity. Logistic regression was used to estimate the association of demographic and behavioral/clinical risk factors (e.g., multimorbidity, perceived disability, body mass index) with PA. Most respondents were females (62%), older (mean age = 68 years) and represented diverse cancer sites, including breast (n = 132), colorectal (n = 102), gynecologic (n = 106), prostate (n = 111), and lung (n = 80). PA participation was mixed; 44% of survivors reported achieving >150 min of aerobic PA, but half of lung and 37% of gynecologic survivors reported no PA (0 min/week). Higher multimorbidity (odds ratio = 0.82, confidence  interval [0.69, 0.98], p < .05), obesity (odds ratio = 0.51, confidence  interval [0.30, 0.86], p < .05), and perceived disability (odds ratio = 0.49, confidence  interval [0.32, 0.77], p < .001) were negatively associated with PA participation. Strength training was suboptimal across all survivors. Most older survivors experienced comorbid conditions, and this was associated with less PA. Survivors who perceived themselves as disabled or who were obese were half as likely as others to participate in PA. This suggests an increasing need to address both physical and psychological limitations in designing PA interventions for real-world needs. Exercise interventions that address the unique needs of older survivors for multimorbidity, obesity, and perceived disability may strengthen opportunities for PA.